Analysis of Forest Vegetation Structure Using the Point Centered Quarter Method - Juliani, Dhesti Novita; Amalia, Lida; Mulyani, Leni Sri; Rusmawan, Chevi Ardiana (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
Pananjung Pangandaran Nature Reserve is a conservation area characterized by high forest vegetation diversity and an important ecological role in maintaining ecosystem stability. Quantitative information on forest vegetation structure is essential as a scientific basis for conservation management. The Point Centered Quarter Method (PCQM) is a widely used vegetation sampling technique for assessing species composition, distribution, and ecological importance in forest communities. This study aimed to analyze the structure and composition of forest vegetation in the Pananjung Pangandaran Nature Reserve using the PCQM. The research was conducted using systematic sampling at ten observation points. At each point, the nearest tree in four quadrants was recorded, resulting in 40 sampled individuals. The collected data were analyzed to calculate Relative Density (RD), Relative Frequency (RF), Relative Dominance (RDo), and the Important Value Index (IVI). The results showed that the forest vegetation consisted of 11 tree species. The species with the highest ecological dominance was Syzygium lateata, exhibiting a high RD, a moderately high RF, a high RDo, and a very high IVI. These values indicate that S. lateata plays a dominant ecological role in the forest community. Furthermore, the identified vegetation structure reflects a relatively uneven species distribution, highlighting the importance of monitoring dominant species to maintain ecosystem balance. This study provides essential ecological information to support conservation planning and sustainable forest management in protected areas.